2016
DOI: 10.1038/ncomms12237
|View full text |Cite
|
Sign up to set email alerts
|

Normal stroma suppresses cancer cell proliferation via mechanosensitive regulation of JMJD1a-mediated transcription

Abstract: Tissue homeostasis is dependent on the controlled localization of specific cell types and the correct composition of the extracellular stroma. While the role of the cancer stroma in tumour progression has been well characterized, the specific contribution of the matrix itself is unknown. Furthermore, the mechanisms enabling normal—not cancer—stroma to provide tumour-suppressive signals and act as an antitumorigenic barrier are poorly understood. Here we show that extracellular matrix (ECM) generated by normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 54 publications
(73 reference statements)
7
102
0
Order By: Relevance
“…Kaukonen et al . showed that breast cancer cells cultured with ECM derived from nonactivated fibroblasts proliferated significantly less than those cultured with an ECM derived from CAFs 120 . Similarly, in comparison with nontransformed fibroblasts, CAFs were able to promote their proliferation of co–cultured SV40 T-immortalized prostate epithelial cells in vitro and to induce tumour growth in vivo when transplanted together in the renal capsule of mice 121 .…”
Section: Stroma–cancer Interactionsmentioning
confidence: 96%
“…Kaukonen et al . showed that breast cancer cells cultured with ECM derived from nonactivated fibroblasts proliferated significantly less than those cultured with an ECM derived from CAFs 120 . Similarly, in comparison with nontransformed fibroblasts, CAFs were able to promote their proliferation of co–cultured SV40 T-immortalized prostate epithelial cells in vitro and to induce tumour growth in vivo when transplanted together in the renal capsule of mice 121 .…”
Section: Stroma–cancer Interactionsmentioning
confidence: 96%
“…Although normal stroma has recently been shown to impede tumorigenesis (Kaukonen et al , 2016), the biophysical and biochemical cues from a tumour microenvironment support malignancy by modulating the hallmarks of cancer (Bissell and Hines, 2011; Pickup et al , 2014). Cancer-associated stromal fibroblasts have been viewed as the protagonists of a dynamically evolving cancer microenvironment and promoters of tumour growth and progression.…”
Section: Integrins and The Tumour Microenvironmentmentioning
confidence: 99%
“…More recently, scaffolding and noncatalytic modes of transcriptional regulation by KDM3A have emerged wherein KDM3A binds to the SWI-SNF (Switch-sucrose nonfermentable) chromatin-remodeling complex (Abe et al, 2015) or Hedgehog-responsive transcription factor GLI1 (Schneider et al, 2015), regulating expression of target genes. Although these functions relate to the role of KDM3A in the nucleus, KDM3A exits the nucleus in response to mechanosensitive stimuli (Kaukonen et al, 2016) and is found at various cytoplasmic sites of somatic cells and during germ cell development (Okada et al, 2007;Yang et al, 2009;Yamada et al, 2012;Kasioulis et al, 2014). Altogether, these findings indicate that KDM3A is a multifunctional protein with highly regulated subcellular distributions and nontranscriptional roles that remain to be explored.…”
Section: Introductionmentioning
confidence: 97%